FAKTOR YANG MEMPENGARUHI MINAT BACA PRAJA IPDN KAMPUS JAKARTA - BOGA PRATALA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
The study discusses on factors that influence the interest of reading of the students of IPDN Campus Jakarta. The research was conducted through a questionnaire method on reading interest given to 50 students of IPDN Campus Jakarta. This research shows a high interest in reading of the students of IPDN Campus Jakarta even though they rarely visit libraries or borrow books and they are often sleepy when reading. It shows the existence of internal factors, including the ended-reading books satisfaction, being diligent, and being able to focus on reading materials. On the other hand, the external factors that affect their reading interests including the book collections they have and the assignment of reading lecture materials given by lecturers. For this reason, the role of lecturers in providing assignments related to reading materials and the role of libraries in providing collections of reading materials is expected to increase the reading interest of the students of IPDN Campus Jakarta. ABSTRAKPenelitian ini membahas tentang faktor yang mempengaruhi minat baca Praja IPDN Kampus Jakarta. Penelitian dilakukan melalui metode kuesioner yang menguji minat baca 50 orang Praja IPDN Kampus Jakarta. Penelitian ini menunjukkan tingginya minat membaca Praja Kampus IPDN Jakarta walaupun mereka jarang mengunjungi perpustakaan ataupun meminjam buku dan sering mengantuk ketika membaca buku. Hal ini menunjukkan adanya faktor internal, diantaranya kepuasan untuk menamatkan membaca buku dan tidak malas, serta mampu memusatkan perhatian kepada bahan bacaan. Di sisi lain, faktor ekternal yang mempengaruhi minat baca mereka diantaranya koleksi buku yang dimiliki dan penugasan membaca materi kuliah yang diberikan oleh dosen. Untuk itu, peran dosen dalam memberikan penugasan terkait materi bacaan dan peran perpustakaan dalam menyedikan koleksi bahan bacaan diharapkan dapat meningkatkan minat baca Praja Kampus IPDN Jakarta ini.